رعاية المصالح في عصر الخلفاء و أثرها في الفقه السياسي المعاصر - الدرديري، أحمد يوسف أحمد (عبد الفتاح محمود ادريس, 2013)
يشير البحث إلى رعاية المصالح في عصر الخلفاء وأثره في الفقه السياسي، فالفقه في جملته أساسه مصالح الأمة، فما هو مصلحة مأمور به، وما هو مضرة منهي عنه، وهذا أصل مقرر مجمع عليه، والمصالح في الشريعة من الموضوعات الدقيقة والضرورية في الحياة الإسلامية والإنسانية عامة، لاندراجها ضمن أهم المباحث الشرعية والأصولية والعقائدية. فالخلفاء أول من قاموا برعاية المصالح في مناهجهم الاجتهادية، فتجددت الوقائع والنوازل، وتوالت الفتوحات الإسلامية، فكان لهذه الاجتهادات آثار عظيمة، بالغة الأهمية في الفقه الإسلامي عموما، فشهدوا التنزيل وعرفوا التأويل، وشهدوا أقضية وفتاوى النبي صلى الله عليه وسلم، فاهتدوا بهديه، فضلا عن أن اجتهاداتهم تحقق المصالح العامة والمقاصد الشرعية، وتضع الإطار لقضية الاجتهاد الشرعي في ضوء مقاصد التشريع ورعاية المصالح. فلا يمكننا أن ننتج فقها حاكما لحركة الفقه السياسي في جميع المجالات ما لم نسترشد بفقه الخلفاء بغرض الإلحاق بالحكم المستجد، ومن خلال النظر إلى مقاصد الشريعة الإسلامية التي تعني رعاية المصالح جلبا ودرءا. This research indicates interests in the era of the caliphs and the impact on the political jurisprudence. Contemporary, fiqh Islamic the in its entirety, based upon the interests of the nation, what is the benefit of unrealized .The evidence came calling, and what is harmful is forbidden, and combined evidence to prevent it. and this out. Complex decision between the Muslim jurists, Vensos Shari'a clearly took into account the interests of. People in this world and in the Hereafter, and interests in Islamic law from the exact topics. And necessary within the Islamic way of life and humanity in general, and the fact that these interests Fell within the most important detective legitimacy and fundamentalism and ideological. Valkhalafa God bless them. Are the first to have sponsored interests into their discretionary after the transfer of the Prophet Muhammad. Upon him to higher ranks, where renewed facts and stalactites, rolled conquests. Islamic and Islamic country area expanded, was for these great interpretations effects, very Important in Islamic jurisprudence and legislation in general, understand who witnessed the download and knew Interpretation And witnessed the districts and the fatwas the Prophet, peace be upon him, Vahtdoa followers, and follow the Sunnah‘In addition, the reasoning to serve the general interests and legitimate purposes, and sets the general framework. The basic plan for the legitimate issue diligence and address issues of renewable communities, in light of. The general purposes of Islamic legislation and interests.We can not produce fabricated and governor of contemporary political jurisprudence movement in all. Areas unless guided by the jurisprudence of the caliphs for the purpose of placement emerging governance, and through consideration. The purposes of Islamic law, which means interests brought ward .
Keywords: المقاصد الشرعية -- الشريعة الاسلامية -- رعاية المصالح -- عصر صدر الاسلام -- الخلفاء الراشدون -- العلماء المسلمون -- القرآن الكريم -- الاجتهاد -- الصحابة و التابعون -- احكام الشريعة -- أصول الفقه